Peningkatan Hasil Belajar PKn Dengan Menggunakan Model Pembelajaran Snowball Throwing - Abdul Manan Siahaan (JURNAL GLOBAL EDUKASI, 2021)
Abstract: Based on the observations of conditions in class VIII.4 SMP Negeri 1 Simpang Empat students were less enthusiastic in asking questions, so an appropriate learning model was used. This research is included in Classroom Action Research with a qualitative approach which was carried out in class VIII .4 SMP Negeri 1 Simpang Empat, totaling 32 students. In the application of Snowball Throwing consists of two cycles. The technique of collecting data on interest in asking questions in this study used an observation sheet for asking questions, and for student learning outcomes using tests in cycles I and II. Data analysis used data reduction, data observation, and drawing conclusions. The results of this study indicate that: (1) the application of the Snowball Throwing learning model increases student activity, (2) the completeness of student learning outcomes in the first cycle test is 68.50%, for the second cycle the completeness increases to 91%, the completeness criteria in the second cycle this is included in the Very Good category, (3) The obstacle experienced by researchers is the lack of seriousness of students in KBM, and the solution is that students must obey the rules of the learning model. Keywords: the development of the 1945 Constitution; social institutions; Snowball Throwing Abstrak: Berdasarkan hasil pengamatan kondisi dalam kelas VIII.4 SMP Negeri 1 Simpang Empat siswa kurang antusias dalam mengajukan pertanyaan, sehingga digunakan model pembelajaran yang sesuai. Penelitian ini termasuk dalam Penelitian Tindakan Kelas dengan pendekatan kualitatif yang dilakukan di kelas VIII .4 SMP Negeri 1 Simpang Empat yang berjumlah 32 siswa. Dalam penerapan Snowball Throwing terdiri dari dua siklus. Teknik pengumpulan data minat bertanya dalam penelitian ini menggunakan lembar observasi minat bertanya, dan untuk hasil belajar siswa menggunakan tes pada siklus I dan II. Analisis data menggunakan reduksi data, observasi data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa: (1) Penerapan model pembelajaran Snowball Throwing meningkatkan keaktifan siswa, (2) Ketuntasan hasil belajar siswa pada tes siklus I adalah 68,50%, untuk tes Siklus II ketuntasan meningkat menjadi 91%, kriteria ketuntasan pada siklus II ini masuk dalam kategori Sangat Baik, (3) Kendala yang dialami peneliti adalah kurangnya keseriusan siswa dalam KBM, dan solusinya siswa harus mentaati aturan model pembelajaran tersebut. Kata Kunci: perkembangan UUD 1945; pranata social; Snowball Throwing